2021
DOI: 10.1530/rep-20-0009
|View full text |Cite
|
Sign up to set email alerts
|

NR5A2 and potential regulatory miRNAs in the bovine CL during early pregnancy

Abstract: Progesterone, which is secreted from the corpus luteum, is indispensable for the establishment and maintenance of pregnancy. The orphan nuclear receptor subfamily 5 group A member 2 (NR5A2) is a regulator of murine luteinization, but neither its regulation nor its role in the fully differentiated, mature corpus luteum (CL) have been described. Therefore, the goal of this study was to profile abundance and investigate the regulation and functions of NR5A2 in the bovine CL. Treatment of cultured luteal steroidog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In the present study, we found that NR5A2 is a transcription factor that plays an important role in regulating cell differentiation, growth, and development [ [52] , [53] , [54] ]. Its activity is regulated by steroid hormones or non-steroid hormones and affects the infiltration and recruitment of peritumoral immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that NR5A2 is a transcription factor that plays an important role in regulating cell differentiation, growth, and development [ [52] , [53] , [54] ]. Its activity is regulated by steroid hormones or non-steroid hormones and affects the infiltration and recruitment of peritumoral immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…NR5A2 can induce transcription in the absence of ligand binding and has an important role in steroidogenesis by regulating key steroidogenic enzymes [28]. NR5A2 is involved in a variety of biological processes such as hepatocyte differentiation, proliferation, liver cholesterol and glucose metabolism, relief of endoplasmic reticulum stress, intestinal glucocorticoid production, pancreatic development and acinar differentiation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma progesterone concentration was measured in all animals to determine the presence and/or maintenance of a functional of corpus luteum during the experimental period. Plasma was isolated by centrifuging 9 mL of blood at 1,500 x g for 15 minutes and progesterone concentration was determined using an ELISA protocol and reagents previously validated for cattle (Hughes et al, 2021). Plasma PAG concentration was measured from day 17 to 20 in animals that received IFNT+PAG to assess movement of PAG across the uterine wall and into the circulation as occurs during pregnancy.…”
Section: Methodsmentioning
confidence: 99%